Right and left solvable extensions of an associative Leibniz algebra. Issue 6 (3rd June 2017) - Shabanskaya, A.
ABSTRACT: A sequence of nilpotent Leibniz algebras denoted by N n, 18 is introduced. Here n denotes the dimension of the algebra defined for n ≥4; the first term in the sequence is ℛ 18 in the list of four-dimensional nilpotent Leibniz algebras introduced by Albeverio et al. [4 ]. Then all possible right and left solvable indecomposable extensions over the field ℝ are constructed so that N n, 18 serves as the nilradical of the corresponding solvable algebras. The construction continues Winternitz' and colleagues' program established to classify solvable Lie algebras using special properties rather than trying to extend one dimension at a time.